2005
DOI: 10.1111/j.0022-202x.2005.23801.x
|View full text |Cite
|
Sign up to set email alerts
|

p63-Specific Activation of the BPAG-1e Promoter

Abstract: p63, a member of the p53 superfamily, is an essential cell fate determinant for stratified epithelium. Deficiency of p63 leads to lack of differentiated epithelium from the skin and the presence of trace undifferentiated cells left in the dermis. We found that transcriptionally active isoforms of p63, TAp63beta and TAp63gamma, activated the skin-specific promoter of bullous pemphigoid antigen 1 (BPAG-1). The p63-response element was localized between bases -177 and -153 upstream of exon 1 in the BPAG-1e promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 47 publications
3
45
0
Order By: Relevance
“…5G). Recently several studies have examined the potential p63 DNA binding consensus sites within p63-responsive genes (14,15,17). In these studies, p63 was shown to preferentially bind to DNA elements that are distinct from the p53 DNA binding element.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5G). Recently several studies have examined the potential p63 DNA binding consensus sites within p63-responsive genes (14,15,17). In these studies, p63 was shown to preferentially bind to DNA elements that are distinct from the p53 DNA binding element.…”
Section: Discussionmentioning
confidence: 99%
“…TAp63g has also been shown to activate the expression of Jagged 1 and Jagged 2, which are involved in Notch signaling, whereas Notch 1 activation has also been shown to suppress DNp63a expression, demonstrating a cross-talk between these pathways (7,8). Additional studies have shown that the biological effects of p63 in development and tumor suppression is exerted through the regulation of multiple signaling pathways (9)(10)(11)(12)(13)(14)(15)(16)(17). p73, another member of the p53 family, was also discovered based on structural similarities to p53 (18).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with 2 known targets of p63, the p21 and BPAG genes (30,31), ChIP efficiencies expressed as a percentage of input chromatin at peak 229 and peak 58 regions were higher than, or at least similar to, those of the known binding sites ( Figure 5C). Use of 2 different p63 antibodies confirmed that the observed binding was specific for p63 ( Figure 5C).…”
Section: Irf6 Expression Is Dependent Upon Functional P63 Having Estab-mentioning
confidence: 91%
“…7C) perp, 91 envoplakin, 69 and BPAG-1. 92 Fig. 8 shows a simplified scheme of the actions of p63 in epidermal development, with particular emphasis on IKKα and K14, although the table does not aim at undermining the importance of other targets.…”
Section: Transcriptional Regulation By P63mentioning
confidence: 99%